Platelet Associated u-PA Up-regulates u-PA Synthesis by Endothelial Cells - Camoin-Jau, L.; Pannell, R.; Anfosso, F; Bardin, N.; Sabatier, F.; Sampol, J.; Gurewich, V.; Dignat-George, F. (Thrombosis and Haemostasis, 2002)
Adhesion of platelets to endothelium has been shown to induce important changes in endothelial properties. In this study, we examined the effect of platelet-endothelial cell interactions on the expression of urokinase-type plasminogen activator (u-PA) by human microvascular endothelial cells. After incubation of endothelial cells with platelets, a dose-dependent increase in the expression of u-PA Ag was observed and reached a plateau for a ratio of 300 platelets per endothelial cells. The u-PA Ag upregulation resulted from an increase in u-PA mRNA that originated from a synthesis by endothelial cells since no u-PA mRNA was detected in platelets. The platelet-induced u-PA synthesis was inhibited when the endothelial cells were pre-treated with phospholipase C to remove the u-PA receptor, or when the platelets were incubated with an antibody that blocks the binding of u-PA to u-PAR. Taken together, these data indicate that u-PA present on the platelet surface interacts with u-PAR on the endothelial cells and induces the u-PA synthesis. This mechanism may represent a physiological control of platelet-mediated intravascular fibrin deposition.
Keywords: Urokinase; platelets; endothelial cells; urokinase-plasminogen receptor